(untitled) - Brown, William H (Belmont, CA, 2005)
An excellent introduction for chemistry, biology, and premed majors, ORGANIC CHEMISTRY, Fifth Edition, delivers cutting-edge coverage that is packed with student-friendly features. Offering a clear presentation, the book offsets reaction mechanisms in a stepwise fashion and emphasizes similarities between related mechanisms. And, for the first time, it introduces organic chemistry of sulfur and phosphorus. ORGANIC CHEMISTRY, Fifth Edition, is renowned for its unified mechanistic themes, emphasis on biological examples, use of applied problems from the pharmaceutical field, and unrivaled full-color visuals. The new fifth edition features increased coverage of bioorganic chemistry, expanded in-text learning tools, and even stronger media integration--including ORGANIC OWL, its powerful Web-based homework system. Numerous resources help ensure student success in the course, including a running margin glossary, an in-text study guide, and more in-chapter examples than any text on the market. The text also emphasizes how-to skills throughout and is packed with challenging synthesis problems as well as medicinal chemistry problems.
Keywords: Chemistry, Organic